2016
DOI: 10.1093/ofid/ofw102
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Dependent Cell-Mediated Cytotoxicity to Hemagglutinin of Influenza A Viruses After Influenza Vaccination in Humans

Abstract: We used an improved ADCC assay to investigate HA-ADCC antibody responses in human sera following either seasonal or avian influenza vaccination. Our results suggest that detection of both neutralizing and non-neutralizing antibodies may better reflect protective capacity of HA-specific antibodies induced by avian influenza vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…These activities are strongly influenced by properties of the Fc domain, including isotype, subclass, and glycan, suggesting the importance of these factors in driving suitable effector function (Barouch et al , ; Gordon et al , ; Huang et al , ). Collectively, there is a rich history of such qualitative antibody characteristics serving as important correlates for control of natural infection and vaccine efficacy (Johnson et al , ; Osier et al , ; Gómez Román et al , ; Weber & Oxenius, ; Ackerman et al , ; Zhong et al , ; He et al , ; Jegaskanda et al , ; Li et al , ; Rouers et al , ). In general, in addition to better distinguishing observed differences in immunity, expanded biophysical analyses of antibody properties can provide a more refined understanding of characteristics important for potent responses and potentially how to improve them.…”
Section: Introductionmentioning
confidence: 99%
“…These activities are strongly influenced by properties of the Fc domain, including isotype, subclass, and glycan, suggesting the importance of these factors in driving suitable effector function (Barouch et al , ; Gordon et al , ; Huang et al , ). Collectively, there is a rich history of such qualitative antibody characteristics serving as important correlates for control of natural infection and vaccine efficacy (Johnson et al , ; Osier et al , ; Gómez Román et al , ; Weber & Oxenius, ; Ackerman et al , ; Zhong et al , ; He et al , ; Jegaskanda et al , ; Li et al , ; Rouers et al , ). In general, in addition to better distinguishing observed differences in immunity, expanded biophysical analyses of antibody properties can provide a more refined understanding of characteristics important for potent responses and potentially how to improve them.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the immunologic basis of protection against heterologous challenge, we attempted to test whether ADCC activity accounted for the cross-protection observed in ferrets. Although our laboratory has recently developed an improved ADCC NK cell activation assay utilizing human NK cell lines as effector cells (Zhong et al, 2016), the assay failed to detect H5-specific ADCC titers in ferret sera, most likely due to the incompatibility of the ferret immunoglobulin Fc region with human NK cell FcγRIIIa receptor (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it remains possible that these in vivo functions of TIV-sera may surface at a different stage of protective immunity or exhibit long-term impact. Indeed, recent studies have shown that ADCC-inducing Abs are readily detectable in normal human sera62, or increased following seasonal influenza vaccine as well as avian influenza vaccine6364. Therefore, further investigation utilizing specific gene-knockout mice will help clarify crucial in vivo CDC or ADCC functions of TIV-sera.…”
Section: Discussionmentioning
confidence: 99%